1997
DOI: 10.1210/endo.138.6.5162
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Steroidogenesis by Chloride Ions in MA-10 Mouse Tumor Leydig Cells: Roles of Calcium, Protein Synthesis, and the Steroidogenic Acute Regulatory Protein*

Abstract: It has previously been shown that omission of extracellular chloride ions during culture of rat Leydig cells markedly enhances LH-stimulated steroidogenesis. In the present study, the mechanisms of the effect of chloride omission on (Bu)2cAMP-stimulated steroidogenesis in MA-10 mouse Leydig tumor cells have been investigated. It was found that chloride omission enhanced progesterone production 2- and 4-fold in the absence and presence, respectively, of submaximally stimulating levels of (Bu)2cAMP (0.1 mM) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In this study, the modulation of steroidogenesis was shown to be affected by the omission of Ca 2+ from the incubation medium in the presence or absence of chloride ions. Using the same experimental paradigms in mouse Leydig cells, a potential link has been demonstrated between steroid synthesis and StAR protein expression, but not with P450scc and 3β-HSD expression, further indicating the direct involvement of StAR in the regulation of steroidogenesis [93].…”
Section: (Iii) Chloride Ionsmentioning
confidence: 88%
See 3 more Smart Citations
“…In this study, the modulation of steroidogenesis was shown to be affected by the omission of Ca 2+ from the incubation medium in the presence or absence of chloride ions. Using the same experimental paradigms in mouse Leydig cells, a potential link has been demonstrated between steroid synthesis and StAR protein expression, but not with P450scc and 3β-HSD expression, further indicating the direct involvement of StAR in the regulation of steroidogenesis [93].…”
Section: (Iii) Chloride Ionsmentioning
confidence: 88%
“…In addition, a chloride channel blocker 4-acetamido-4'-isothiocyanatostilbene-2-2'-disulphonic acid inhibited LH induced steroidogenesis with the former condition, suggesting the independent involvement of chloride channels and cAMP pathways [241]. The omission of extracellular Cl -has been demonstrated to enhance steroid synthesis in response to submaximal cAMP analog treatment in MA-10 cells [93]. In this study, the modulation of steroidogenesis was shown to be affected by the omission of Ca 2+ from the incubation medium in the presence or absence of chloride ions.…”
Section: (Iii) Chloride Ionsmentioning
confidence: 93%
See 2 more Smart Citations
“…Hormonal signal transduction and steroidogenesis can be affected by changes in intracellular and extracellular concentrations of inorganic ions, cellular resting membrane potential, and cell size [29,30,35,54-59]. Blockade of 4-AP sensitive K + channels in non-nerve, non-muscle cells can lead to changes in transmembrane ion gradients, membrane potential and cell volume [42,60].…”
Section: Resultsmentioning
confidence: 99%